Masters of war : classical strategic thought - Handel, Michael I. (London : Frank Cass Publishers, 2001)
This study is based on a detailed textual analysis of the classical works on war, the central conclusion being that the logic of waging war and of strategic thinking is as universal and timeless as human nature itself.
Strategy : past theories, modern practice -- Comparing Sun Tzu and Clausewitz -- The definition of war : a question of the level of analysis -- Clausewitz and Mao Tse-tung on theory and practice in war -- "Attacking the enemy's plans" and the concept of "the center of gravity" : Eastern psychology and Western mechanics -- The primacy of politics and the military commander -- The rational calculus of war : correlating ends and means -- Clausewitz on the role of "moral forces" in war -- The supreme act of judgment : understanding the "nature of war" and the "trinitarian analysis" -- The first element of the remarkable trinity : the people in arms -- The ideal and the real : victory without bloodshed and the search for the decisive battle -- Speed, numerical superiority, and victory -- The principle of continuity and the culminating point of victory : the contradictory nature of war -- Clausewitz on war termination -- Deception, surprise, and intelligence -- On military leadership -- Boldness and calculation -- Corbett, Clausewitz, and Sun Tzu -- Conclusions : towards a unified theory of war -- Appendix A. Contradiction and paradox in the theory of war -- Appendix B. The Weinberger Doctrine -- Appendix C. Clausewitz's ideal-type method applied to Sun-Tzu's The art of war -- Appendix D. Clausewitz's On war as a gestalt or a systemic theory -- Appendix E. The problem of the level of analysis and the 'Tacticization of strategy' -- Appendix F. Clausewitz and the principle of concentration.
Includes bibliographical references and index.
Keywords: Sunzi, -- active 6th century B.C.; Clausewitz, Carl von, -- 1780-1831.; Jomini, Antoine Henri, -- baron de, -- 1779-1869.; Sun Zi; Clausewitz, Carl von, -- 1780-1831.; Sunzi, -- 6e s. av. J.-C.; Clausewitz, Carl von, -- 1780-1831.; Jomini, Antoine Henri, -- baron de, -- 1779-1869.; Clausewitz, Carl von -- 1780-1831; Jomini, Antoine Henri de -- 1779-1869; Sun, Wu -- ca. v500; Clausewitz, Carl von, -- 1780-1831.; Sunzi, -- active 6th century B.C.; Jomini, Antoine Henri, -- baron de, -- 1779-1869.; Sun Zi, -- 6e s. av. J.-C.; Clausewitz, Carl von, -- 1780-1831.; 2; Sunzi bing fa (Sunzi); Vom Kriege (Clausewitz, Carl von); Military art and science -- History; Art et science militaires -- Histoire; Military art and science; Geschichte; 2; Strategie; Militaire strategie; 2; Military art and science; Art militaire; 2; History; 2